2015
DOI: 10.1103/physrevlett.115.067201
|View full text |Cite
|
Sign up to set email alerts
|

Large Superconducting Spin Valve Effect and Ultrasmall Exchange Splitting in Epitaxial Rare-Earth-Niobium Trilayers

Abstract: Epitaxial Ho/Nb/Ho and Dy/Nb/Dy superconducting spin valves show a reversible change in the zero-field critical temperature (ΔT(c0)) of ∼400  mK and an infinite magnetoresistance on changing the relative magnetization of the Ho or Dy layers. Unlike transition-metal superconducting spin valves, which show much smaller ΔT(c0) values, our results can be quantitatively modeled. However, the fits require an extraordinarily low induced exchange splitting which is dramatically lower than known values for rare-earth F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 47 publications
4
27
0
3
Order By: Relevance
“…However, when there are two or more F layers with non-collinear exchange fields, as can happen for example in F 1 /F 2 /S structures, S z cannot commute with the Hamiltonian and the m z = ±1 triplet states can also be induced. This is also the case with a single F layer having a non-uniform magnetization texture [18][19][20] . In contrast to the short-range proximityinduced singlet pair amplitudes, these odd m z = ±1 triplet states are usually long ranged [21][22][23][24][25][26][27] in the F layers.…”
Section: Introductionmentioning
confidence: 87%
“…However, when there are two or more F layers with non-collinear exchange fields, as can happen for example in F 1 /F 2 /S structures, S z cannot commute with the Hamiltonian and the m z = ±1 triplet states can also be induced. This is also the case with a single F layer having a non-uniform magnetization texture [18][19][20] . In contrast to the short-range proximityinduced singlet pair amplitudes, these odd m z = ±1 triplet states are usually long ranged [21][22][23][24][25][26][27] in the F layers.…”
Section: Introductionmentioning
confidence: 87%
“…For example, Gu et al demonstrated that an antiferromagnetic to ferromagnetic transition in Ho resulted in modification of the T c of an adjacent Nb layer of over 100 mK, however the exact mechanism involved in the T c shift was not established [22]. This work was later expanded by producing trilayer samples of Ho/Nb/Ho and Dy/Nb/Dy in which a spin valve like effect of 400 mK was discovered [23]. These works established the ability to control T c with the ferromagnetic texture in rare-earth ferromagnets, however lacked the theoretical description and the additional modification to the shape of the R(T) transition reported in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the optimal operational field for this device is of the order of 20 kOe. Gu et al [10,11] reported ∆T c ∼ 400 mK for Ho/Nb/Ho trilayers. Also in this case the parallel configuration of magnetizations was reached at a field of ∼ 10 kOe.…”
mentioning
confidence: 99%